Non-coding RNAs in ossification of the posterior longitudinal ligament - Zhang, Haoran; Zhang, Qingyu; Yuan, Zenong; Dong, Jun (Frontiers in Genetics, 2022)
Ossification of the posterior longitudinal ligament (OPLL) is a kind of disease that involves a variety of factors leading to ectopic bone deposition of the spinal ligament. Although the detailed mechanism is not clear, genetic factors play important roles in the development of this disease. Noncoding RNA (ncRNA) refers to an RNA molecule that is not translated into a protein but participates in the regulation of gene expression. Functionally important types of ncRNA associated with OPLL include long noncoding RNA, microRNA, and circular RNA. We listed the differentially expressed ncRNAs in OPLL patients and normal controls to find the ncRNAs most relevant to the pathogenesis of the disease. The potential regulatory networks of ncRNA in OPLL cells were analyzed based on their most abundant signal transduction pathway data. The analysis of the highly connected ncRNAs in the regulatory network suggests that they play an important role in OPLL. These findings provide new directions for the study of OPLL pathogenesis and therapeutic targets. In this paper, we reviewed and analyzed the literature on ncRNAs in OPLL published in recent years, aiming to help doctors better understand and treat this disease.